SEKOLAH DASAR ISLAM (SDI) BERKARAKTER ‘FULL DAY SCHOOL’ DAN MADRASAH IBTIDAIYAH (MI) DI MATA MASYARAKAT - *, Salafudin (Jurnal Penelitian, 2010)
Islamic school, including Madrasah Ibtida’iyah (Islamic Elementary School), has been identified as a traditional school with lack of facilities, excessive focus on Islamic studies and less focus on science in its curriculum. That’s why, its quality are doubted and questioned, which is proportional with its cheap tuition, and uninterested. The appearing of Islamic school labelled “Full Day School”, especially in elementary school. In particular, it fulfills the expectation of pupils and their parent on the high quality of school, with a number of facilities and good mixing and fusing of Islamic studies and sciences in comprehensive curriculum. This school type could be the best one of alternative schools to be chosen. Using descriptive approach, this qualitative research was aimed to describe Madrasah Ibtidaiyah (Traditional Islamic Elementary School) and the Full Day School of Sekolah Dasar Islam (Modern Islamic Elementary School) in people’s perspective, and searched their expectation on high quality of Islamic school. So, the data were acquired purposively. This research was located in Pekalongan City